2022
DOI: 10.3390/cancers14071605
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Patterns in Care Utilization and Financial Distress between Patients with Blood Cancers and Solid Tumors: A National Health Interview Survey Study, 2014–2020

Abstract: Introduction: Important differences exist between the presentation, treatment, and survivorship of patients and survivors with blood cancers. Furthermore, existing research in financial toxicity has not fully addressed the relationship between medical care utilization and patient-reported outcomes of financial barriers and distress. We answered these questions by using a nationally representative survey. Methods: Respondents with blood cancers and solid tumors from the National Health Interview Survey were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…15,16 Regardless of the health care system, 17,18 it has been observed that patients with hematologic cancers have higher level of medical care utilization and financial hardship in affording care compared with patients with solid tumors. 19 This may be due to frequent need for blood and platelet transfusion support requiring visits to the clinic, the high prevalence of fatigue that may limit the capacity to work, or the long periods of hospitalization to recover from intensive chemotherapy. 20 Because of these differences, dedicated analyses and interventions on FT experienced by patients with hematologic malignancies are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Regardless of the health care system, 17,18 it has been observed that patients with hematologic cancers have higher level of medical care utilization and financial hardship in affording care compared with patients with solid tumors. 19 This may be due to frequent need for blood and platelet transfusion support requiring visits to the clinic, the high prevalence of fatigue that may limit the capacity to work, or the long periods of hospitalization to recover from intensive chemotherapy. 20 Because of these differences, dedicated analyses and interventions on FT experienced by patients with hematologic malignancies are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although clinicians recognize fundamental differences between the treatment landscape of solid tumors and hematologic malignancies-for instance, radiation and surgery as options for solid tumors versus months long inpatient admissions for leukemia induction chemotherapy-there are other distinct differences in health care utilization and end-of-life care. Despite accounting for only about 10% of all patients with cancer, 8 patients with hematologic malignancies demonstrate different care utilization patterns 9,10 and use more aggressive medical care and less hospice services at the end of life compared with patients with solid tumors. 11,12 Therefore, dedicated interventions targeted at alleviating the financial burden experienced by patients with hematologic malignancies are timely and necessary.…”
mentioning
confidence: 99%